Maximizing the impacts of academic research - Samantha Jane Ahern (Association for Learning Development in Higher Education (ALDinHE), 2021)
A Book review of Dunleavy, P. and Tinkler, J. (2021) Maximizing the impacts of academic research. London: Red Globe Press